2012
DOI: 10.4156/ijact.vol4.issue4.2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bee Colony Algorithm for Portfolio Optimization Problems

Abstract: In this paper, a cardinality constrained mean-variance model is introduced for the portfolio optimization problems. This model is a mixed quadratic and integer programming problem for which efficient algorithms do not exist. The use of heuristic algorithms in this case is necessary. Some studies have investigated the cardinality constrained mean-variance model using heuristic algorithm. But almost none of these studies deal with artificial bee colony algorithm. The purpose of this paper is to use artificial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…SIA involves the collective study of the individuals behavior of the population interact with one another locally. The study has been done to solve the portfolio optimization problem using SIA (Deng et al , 2012; Koshino et al , 2007; Zhu et al , 2011; Ni et al , 2017; Haqiqi and Kazemi, 2012; Li et al , 2012; Wang et al , 2012; Tuba and Bacanin, 2014a, b; Kalayci et al , 2017; Gao et al , 2018; Suthiwong et al , 2019). PSO (Koshino et al ., 2007) proposed a combination of the inertia weights approach and the constriction factor approach to solve the portfolio selection problem with the aim of ranking individuals in the population.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…SIA involves the collective study of the individuals behavior of the population interact with one another locally. The study has been done to solve the portfolio optimization problem using SIA (Deng et al , 2012; Koshino et al , 2007; Zhu et al , 2011; Ni et al , 2017; Haqiqi and Kazemi, 2012; Li et al , 2012; Wang et al , 2012; Tuba and Bacanin, 2014a, b; Kalayci et al , 2017; Gao et al , 2018; Suthiwong et al , 2019). PSO (Koshino et al ., 2007) proposed a combination of the inertia weights approach and the constriction factor approach to solve the portfolio selection problem with the aim of ranking individuals in the population.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have been presented a cluster-based ACO algorithm for portfolio selection using an iterative k -means method to optimize the Sharpe ratio. In the domain, implementations of an artificial bee colony (ABC) for portfolio problems can be found (Wang et al , 2012; Tuba and Bacanin, 2014a, b). The authors have proposed an integrated method-based ABC to solve the portfolio section problem with cardinality constrained.…”
Section: Related Workmentioning
confidence: 99%
“…The results show that the average return of a portfolio in the trading bubble space at a certain level of risk is greater than that of a non-bubble portfolio, based on subjective accounting. Wang et al . (2012) compared the bee colony algorithm (ABC) with the GA, tabu search (TS), simulated repayment (SA), and PSO algorithms and reported that the bee colony algorithm performed well in solving the portfolio optimization problem and obtained better solutions than other heuristic algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%